2017
DOI: 10.1038/s41598-017-14186-2
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off between cognitive and physical performance, with relative preservation of brain function

Abstract: Debate surrounds the issue of how the large, metabolically expensive brains of Homo sapiens can be energetically afforded. At the evolutionary level, decreased investment in muscularity, adiposity and the digestive tract allow for a larger brain. Developmentally, high neo-natal adiposity and preferential distribution of resources to the brain provide an energetic buffer during times of environmental stress. Through an experimental design, we investigated the hypothesis of a trade-off involving brain and muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 74 publications
(65 reference statements)
4
29
1
Order By: Relevance
“…An experimental design applied to a sporting contest was employed to investigate the hypothesis of a trade‐off involving the brain at the acute, rather than the evolutionary or developmental, level. Simultaneous challenge of both cognitive and physical functions resulted in relative preservation of cognitive function over physical power output (Longman, Stock, & Wells, ), lending support to the selfish brain hypothesis (Peters et al, ) and highlighting the metabolically privileged niche occupied by the human brain. This metabolic hierarchy may be an evolved trait, as the chances of survival may be boosted more by a well‐fuelled brain than well‐fuelled muscles when facing an environmental challenge (Beedie & Lane, ).…”
Section: Ultra‐endurance Sport As a Model To Study Human Life Historymentioning
confidence: 87%
“…An experimental design applied to a sporting contest was employed to investigate the hypothesis of a trade‐off involving the brain at the acute, rather than the evolutionary or developmental, level. Simultaneous challenge of both cognitive and physical functions resulted in relative preservation of cognitive function over physical power output (Longman, Stock, & Wells, ), lending support to the selfish brain hypothesis (Peters et al, ) and highlighting the metabolically privileged niche occupied by the human brain. This metabolic hierarchy may be an evolved trait, as the chances of survival may be boosted more by a well‐fuelled brain than well‐fuelled muscles when facing an environmental challenge (Beedie & Lane, ).…”
Section: Ultra‐endurance Sport As a Model To Study Human Life Historymentioning
confidence: 87%
“…The current study The current study sought to utilise multi-day ultra-marathons in hot and cold environments to investigate whether the morphologies predicted by Bergmann's and Allen's rules confer a functional benefit in thermally challenging environments. This investigation stems from a wider research theme using contemporary sports as a tool to examine evolutionary theory (Longman et al 2015(Longman et al , 2017a(Longman et al , 2018.…”
Section: Physical Activity Thermoregulation and Morphological Adaptamentioning
confidence: 99%
“…() demonstrated energetic trade‐offs between brain and body development by showing that a reduced rate of body growth accompanied the highest rates of brain development in children. Another recent study (Longman, Stock & Wells, ) demonstrated acute energetic trade‐offs between mental performance and physical performance in male athletes.…”
Section: Introductionmentioning
confidence: 95%